Acid-mediated topological control in a functionalized foldamer. Issue 39 (5th April 2016) - Knipe, Peter C.; Thompson, Sam; Hamilton, Andrew D.
Abstract : Protonation mediates the transition between linear and helical foldamer topologies giving rise to a dynamic, functionalized molecular surface. Abstract : Induced conformational change provides a powerful mechanism to modulate the structure and function of molecules. Here we describe the synthesis of chiral, surface-functionalized oligomeric pyridine/imidazolidin-2-one foldamers, and interrogate their acid-mediated transition between linear and helical topologies.